Pelaksanaan Penilaian Autentik Kurikulum 2013 di Sekolah Dasar - Handayani, Sri; Mustika, Dea (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This study aims to describe authentic assessment in 2013 curriculum learning at SDN 13 Beauty. The design of this study used a descriptive approach and method. The resource persons in this study involved 3 class teachers, namely class II, IV, and class V teachers at SDN 13 Belutu. Data collection techniques used are interviews, observation, and documentation. The data analysis technique used the Milles and Huberman model. The results showed that the teacher assessed authenticity as seen from 3 aspects of competence, namely aspects of attitude, knowledge, and skills competence. In the implementation of the attitude assessment, the teacher assesses the student's attitude using direct observation (observation), then the teacher records the attitude in the teacher's journal. In the implementation of knowledge assessment, the teacher assesses students' knowledge by using written, oral, and task test techniques. Knowledge assessment is also carried out during the Daily Assessment (PH), Mid-Semester Assessment (PTS), and Final Semester Assessment (PAS). During the implementation of PH, PTS, and PAS, the form of the test used was multiple choice and explanation. Then, in the skills assessment, the teacher assesses the students' skills using practical techniques and products. The assessment instrument used by the teacher is in the form of an assessment rubric in the teacher's book and student's book. From the results of this study, it can be said that SDN 13 Belutu has carried out an authentic assessment of 2013 curriculum learning.